Assessing Teaching Strategies of Stem Courses During Covid-19 Pandemic: A Comparison Study in Performance and Learning Experience Between Synchronous and Asynchronous Learning Mode in Higher Institution (Proceedings of the International Conference on Future of Education, 2022)
The COVID-19 crisis has forced lecturers around the world to shift from traditional into computer screens classroom. Here, various teaching strategies adopted to support this adhoc virtual learning environment. Despite the various efforts to solve the challenges among the different teaching strategies implemented, the efficiency of the strategies is still questionable. Hence, the aim of this study is to investigate the most suitable teaching strategies for STEM online education. This study presents a comparison of two different learning modes, synchronous and asynchronous mode, in terms of students' performance and learning experience in science, technology, engineering and mathematics (STEM) courses. Two STEM courses were selected: engineering and programming course. The study randomly assigned students to one of two conditions: (i) taking the course in synchronous mode - class conducted in real-time mode with lecturers via online meetings and (ii) taking the same course in asynchronous mode – online materials being provided in advance such as pre-recorded video content. Here, the course content (learning outcomes, course topics required literature and assessment) were identical for all students. Next, all students sit for an (i) assessment to assess their mastery of the course content, (ii) completed an entrance-exit survey and (iii) a   self-reported satisfaction questionnaire about their learning experience and satisfaction. Content analysis has been conducted to see the relationship between student scores, learning experience and satisfaction. The results showed that there are differences of a correlation between these three factors. This study contributes to identifying the most suitable teaching strategy as well as increasing the efficiency of online learning in the context of STEM education in higher institutions.
Keywords: COVID-19; STEM; teaching methodology; online learning; higher institution